Answer:
(k ∘ p)(x)=2x^2-12x+13
Step-by-step explanation:
(k ∘ p)(x)=k(p(x))
(k ∘ p)(x)=k(x-3)
(k ∘ p)(x)=2(x-3)^2-5
(k ∘ p)(x)=2(x-3)(x-3)-5
Use foil on (x-3)(x-3) or use this as a formula:
(x+a)^2=x^2+2ax+a^2.
(k ∘ p)(x)=k(p(x))
(k ∘ p)(x)=k(x-3)
(k ∘ p)(x)=2(x-3)^2-5
(k ∘ p)(x)=2(x-3)(x-3)-5
(k ∘ p)(x)=2(x^2-6x+9)-5
Distribute: multiply terms inside ( ) by 2:
(k ∘ p)(x)=2x^2-12x+18-5
(k ∘ p)(x)=2x^2-12x+13
The composite function is [tex]k(p(x))=2x^{2} -12x+13[/tex]
Option b is correct.
Composite function :
Given function are,
[tex]k(x)=2x^{2} -5,p(x)=(x-3)[/tex]
We have to find composite function [tex]k(p(x))[/tex].
[tex]k(p(x))=k(x-3)\\\\k(p(x))=2(x-3)^{2}-5\\ \\k(p(x))=2(x^{2} +9-6x)-5\\\\k(p(x))=2x^{2} +18-12x-5\\\\k(p(x))=2x^{2} -12x+13[/tex]
Thus, the composite function is [tex]k(p(x))=2x^{2} -12x+13[/tex]
Learn more about the composite function here:
https://brainly.com/question/10687170
If u(x)=-2x^2+3 and (x)=1/x, what is the range of (u°v)(x)
Answer:
The range is all real number y<3.
Step-by-step explanation:
[tex](u \circ v)(x)=u(v(x))[/tex]
So we have to have v(x) exist for input x.
Let's think about that. v(x)=1/x so the domain is all real numbers except 0 since you cannot divide by 0. v(x)=1/x will also never output 0 because the numerator of 1/x is never 0. So the range of v(x)=1/x is also all real numbers except y=0.
Now let's plug v into u:
[tex]u(x)=-2x^2+3[/tex]
[tex]u(v(x))=u(\frac{1}{x}[/tex]
[tex]u(v(x))=-2(\frac{1}{x})^2+3[/tex]
The domain of will still have the restrictions of v; let's see if we see any others here.
Nope, there are no, others, the only thing that is bothering this function is still the division by x (which means we can't plug in 0).
[tex]u(v(x))=\frac{-2}{x^2}+3[/tex]
Let's thing about what are y's value will not ever get to be.
Let's start with that fraction. -2/x^2 will never be 0 because -2 will never be 0.
So we will never have y=0+3 which means y will never be 3.
There is one more thing to notice -2/x^2 will never be positive because x^2 is always positive and as we know a negative divided by a positive is negative.
So we have (a always negative number) + 3 this means the range will only go as high as 3 without including 3.
The range is all real number y<3.
4.
A 48 inch long cylindrical shaped cannon has a diameter of 4 inches. There are two 3 inch diameter cannonballs inside it. How much empty space is in the cannon barrel (round to the nearest hundredth and use 3.14 for pi)?
Answer:
[tex]574.62\ in^3[/tex]
Step-by-step explanation:
First we calculate the volume of the cylinder.
[tex]V=\pi r^2*l[/tex]
Where r is the radius and l is the length of the cylinder.
We know that:
[tex]r = \frac{diameter}{2}[/tex]
[tex]r = \frac{4}{2}[/tex]
[tex]r = 2\ in[/tex]
Then:
[tex]V=3.14* 2^2*48[/tex]
[tex]V=602.88\ in^3[/tex]
Assuming that the cannon balls are spherical then the volume of the 2 spheres is:
[tex]V=2*\frac{4}{3}\pi r^3[/tex]
[tex]V=2*\frac{4}{3}(3.14)(\frac{3}{2})^3[/tex]
[tex]V=2*\frac{4}{3}(3.14)(\frac{3}{2})^3[/tex]
[tex]V=28.26\ in^3[/tex]
So the space left inside the cannon is
[tex]V=602.88\ in^3 - 28.26\ in^3\\\\V=574.62\ in^3[/tex]
How many units away is 1 from -6 on a number line?
-7
-5
5
7
Answer:
-7
Step-by-step explanation:
Lets count back.
1,0,-1,-2,-3,-4,-5,-6
We are going back, so -7
Which is the inverse of the function f(x)=1/3x+5
Answer:
f-¹(x) =(1-5x) /3x.
Step-by-step explanation:
f(x)=1/(3x+5)
Let y=1/(3x+5)
Exchanging x and y,
x=1/(3y+5)
3y+1=1/x
3y=1/x-5
3y=(1-5x) /x
y=(1-5x)/3x
f-¹(x) =(1-5x) /3x.
Answer:
y=3(x-5)
Step-by-step explanation:
The ratio of boys to girls in a school is 5:8. If the number
of girls exceeds the number of boys by 144, calculate the
total number of students in the school.
helpppp! The population of a town is 20,000 people in the year 2000. How many people with live in the town in 2016 if the population increases at a rate of 6% every 2 years? Round your answer to the nearest whole number.
Answer:
31877 people with live in the town in 2016 if the population increases at a rate of 6% every 2 years
Step-by-step explanation:
The formula used will be
A(t) = P(1+r)^t
A(t) = Future value
P = population
r = rate
t = time
P= 20,000
r =6% or 0.06
t = 16
Since population is increased every 2 years, so t = 16/2 = 8
Putting value:
A(16) = 20,000(1+0.06)^8
A(16)= 20,000(1.06)^8
A(16) = 31876.9 ≈ 31877
So, 31877 people with live in the town in 2016 if the population increases at a rate of 6% every 2 years
if angle a is 50° and angle b is 75° what is the measurement of angle c
Answer:
m∠C = 55°
Step-by-step explanation:
A triangle's sum of all angles = 180°
Set the equation: m∠A + m∠B + m∠C = 180°
m∠A = 50° ; m∠B = 75°
Plug in the corresponding numbers to the corresponding variables:
50 + 75 + m∠C = 180
Simplify. Combine like terms:
(50 + 75) + m∠C = 180
125 + m∠C = 180
Isolate the variable. Note the equal sign, what you do to one side, you do to the other. Subtract 125 from both sides:
m∠C + 125 (-125) = 180 (-125)
m∠C = 180 - 125
m∠C = 55
m∠C = 55°
Check: All the angles added together must equal 180°:
50 + 75 + 55 = 180
125 + 55 = 180
180 = 180 (True)
~
What is the shaded portion of the circle
Answer:
[tex](5\pi-11.6)\ ft^{2}[/tex]
Step-by-step explanation:
we know that
The area of the shaded region is equal to the area of the sector minus the area of the triangle
step 1
Find the area of the circle
the area of the circle is equal to
[tex]A=\pi r^{2}[/tex]
we have
[tex]r=5\ ft[/tex]
substitute
[tex]A=\pi (5)^{2}[/tex]
[tex]A=25\pi\ ft^{2}[/tex]
step 2
Find the area of the sector
we know that
The area of the circle subtends a central angle of 360 degrees
so
by proportion find out the area of a sector by a central angle of 72 degrees
[tex]\frac{25\pi}{360}=\frac{x}{72}\\ \\x=72*25\pi /360\\ \\x=5\pi\ ft^{2}[/tex]
step 3
Find the area of triangle
The area of the triangle is equal to
[tex]A=\frac{1}{2}(2.9+2.9)(4)= 11.6\ ft^{2}[/tex]
step 4
Find the area of the shaded region
Subtract the area of the triangle from the area of the sector
[tex](5\pi-11.6)\ ft^{2}[/tex]
which function has a vertex at the origin
In Mathematics, quadratic functions such as y=ax^2 and cubic functions such as y=ax^3, will have their vertex at the origin, represented by (0,0). These functions show this characteristic because there are no shifts involved in the equation.
Explanation:In Mathematics, there are different functions that can have their vertex at the origin (0,0). For instance, when we speak of quadratic functions, a function in the form of y = ax^2 will have its vertex at the origin as it's a parabola that opens upward or downward.
Similarly, for the case of cubic functions, a function in the form of y = ax^3 will have the vertex at the origin.
Important to note is that, for all these cases, the vertex is at the origin because there are no horizontal or vertical shifts involved in the equation. That is, the h & k in (x-h)^2+k and (x-h)^3+k are both zero.
Learn more about Vertex at Origin here:https://brainly.com/question/35531100
#SPJ6
please help me wiht this question
Check the picture below.
What is the slope of the line that passes through the pair of points?
(-2,7), (18, 1)
Answer:
Your slope of the line is -3/10.
Step-by-step explanation:
Use the following equation:
m (slope) = (y₂ - y₁)/(x₂ - x₁)
Let:
(x₁ , y₁) = (-2 , 7)
(x₂ , y₂) = (18 , 1)
Plug in the corresponding numbers to the corresponding variables:
m = (1 - 7)/(18 - (-2))
Simplify. First solve the parenthesis, then divide:
m = (-6)/(18 + 2)
m = -6/20
Simplify.
m = (-6/20)/(2/2) = -3/10
Your slope of the line is -3/10.
~
Answer:
[tex]\displaystyle \frac{-3}{10}[/tex]
Step-by-step explanation:
Slope formula:
[tex]\displaystyle \frac{y_2-y_1}{x_2-x_1}[/tex]
[tex]\displaystyle\frac{1-7}{18-(-2)}= \frac{-6}{20}=\frac{-6\div2}{20\div2}=\frac{-3}{10}=-\frac{3}{10}[/tex]
Therefore, the slope is -3/10, and the correct answer is -3/10.
How to work out 161 as a percentage of 3500
Answer:
161 is 4.6% of 3500
Step-by-step explanation:
Divide:
161
-------- = 0.046
3500
Now multiply this result by 100%: 4.6%.
161 is 4.6% of 3500.
Answer:
4.6%
Step-by-step explanation:
To find what percent number A is of number B, divide A by B and multiply by 100.
To find what percent 161 is of 3500, divide 161 by 3500 and multiply by 100.
percent = 161/3500 * 100 = 0.046 * 100 = 4.6%
161 is 4.6% of 3500
ANSWER ASAP PLEASE!!
Clayton needs to reflect the triangle below across the line y=x
Which statements about the reflection are true? Check all that apply.
Clayton could use the relationship (x,y)→ (y,x) to find the points of the image.
Clayton could negate both the x and y values in the points to find the points of the image.
C’ will remain in the same location as C because it is on the line of reflection.
C’ will move because all points move in a reflection.
The image and the pre-image will be congruent triangles.
The image and pre-image will not have the same orientation because reflections flip figures.
Answer:
Clayton could use the relationship (x,y)→ (y,x) to find the points of the image
C’ will remain in the same location as C because it is on the line of reflection
The image and the pre-image will be congruent triangles
The image and pre-image will not have the same orientation because reflections flip figures
Step-by-step explanation:
Verify each statement
case A) Clayton could use the relationship (x,y)→ (y,x) to find the points of the image
The statement is true
we know that
The rule of the reflection of a point across the line y=x is equal to
(x,y)→ (y,x)
case B) Clayton could negate both the x and y values in the points to find the points of the image
The statement is false
case C) C’ will remain in the same location as C because it is on the line of reflection
The statement is true
If a point is on the line of reflection (y=x), then the point remain in the same location because the x and y coordinates are equal
case D) C’ will move because all points move in a reflection
The statement is false
Because C' is on the line of reflection (y=x), then the point remain in the same location
case E) The image and the pre-image will be congruent triangles
The statement is true
Because the reflection not change the length sides of the triangle or the measure of its internal angles. Reflection changes only the orientation of the figure
case F) The image and pre-image will not have the same orientation because reflections flip figures
The statement is true
Because in a reflection across the line y=x, the x coordinate of the pre-image becomes the y-coordinate of the image and the y-coordinate of the pre-image becomes the x-coordinate of the image
Give the equation of the line passing through the point (3,−21) that is parallel to
y= −5x+9.
Answer:
y=-5x-6
Step-by-step explanation:
Parallel means you are looking for an equation that has the same slope as the one given.
The slope of y=-5x+9 is -5.
All I did was compare it to y=mx+b where m is slope and b is y-intercept.
So our equation is in the form y=-5x+b.
We want to find b such that y=-5x+b goes through (3,-21).
So we can plug in our point that is on this line so that that happens.
-21=-5(3)+b
-21=-15+b
Add 15 on both sides
-6=b
b=-6
So the line that is parallel to y=-5x+9 while going through (3,-21) is y=-5x-6.
Factor the polynomials 2x4+4x3+6x2?
Answer:x^2+2x+3
Step-by-step explanation:
I’m assuming you meant 2x^4+4x^3+6x^2...
So you can pull out 2x^2 from all of the polynomials...
And this equation isn’t able to be simplified anymore. Hope this helps!
The polynomial 2x^4 + 4x^3 + 6x^2 is factored by first finding the GCF 2x^2, resulting in 2x^2(x^2 + 2x + 3). The quadratic inside the parentheses cannot be factored further with real coefficients.
Explanation:To factor the polynomial 2x^4 + 4x^3 + 6x^2, we first look for the greatest common factor (GCF) that can be factored out. In this case, each term has at least a factor of 2 and an x^2. Factoring out the GCF, we get:
2x^2(x^2 + 2x + 3)
Now, we look at the quadratic inside the parentheses to see if it can be factored further. However, the quadratic x^2 + 2x + 3 does not factor neatly over the integers because the discriminant, b^2 - 4ac, is negative (2^2 - 4(1)(3) = 4 - 12 = -8). Since we are only looking for real coefficients and not complex ones, we conclude that the quadratic cannot be factored further, and so the polynomial is fully factored as 2x^2(x^2 + 2x + 3).
I need help plz. Show your work! 23 + 5 x 3 - 100 + 19 in PEMDAS!
Answer:
-43
Step-by-step explanation:
Follow PEMDAS as well as the left -> right rule.
Note that: PEMDAS =
Parenthesis
Exponents (& Roots)
Multiplication
Division
Addition
Subtraction
First, solve the multiplication:
23 + (5 * 3) - 100 + 19
23 + (15) - 100 + 19
Simplify. Follow the left-> right rule:
(23 + 15) - 100 + 19
38 - 100 + 19
(38 - 100) + 19
-62 + 19 = -43
-43 is your answer.
~
Answer:
-43
Step-by-step explanation:
Steps to PEMDAS:
P: parenthesis - There are no parenthesis in this equation.
E: exponents - There are no exponents in this equation.
M: multiplication 5 x 3 = 15
D: division There is no division in this equation.
A: addition 23 + previous 15 + 19 = 57
S: subtraction Previous answer 57 - 100 = -43
Therefore, the answer is -43.
Which function in vertex form is equivalent to fx = 4+x2-2x
Answer:
f(x) = (x-1)² + 3
Step-by-step explanation:
f(x) = 4+x²-2x or f(x) = x²- 2x + 4 -----> eq 1
consider the top-most choice
f(x) = (x-1)² + 3 = x² + 2·x·(-1) + 1² + 3
f(x) = x² - 2x+ 1 + 3
f(x) = x² - 2x+ 4 -----> compare this with eq 1 above (they match!)
hence f(x) = (x-1)² + 3 is the answer
Tom drank 1 1/4 quarts of water and his sister Jane drank 1.75 quarts of water. Write the amount that Jane drank using a
fraction. Who drank more water?
(Doesn’t have choices)
Answer:
Jane drank 1 3/4 quarts of water.
Jane drank more water than Tom
Step-by-step explanation:
Tom drank = 1 1/4 quarts of water
Jane drank = 1.75 quarts of water
We have to write the amount of water Jane drank in fraction.
There are some steps to convert decimal into fraction.
Step 1:
Value is 1.75:
Put the 1 aside and just work on 0.75
Write down the decimal value divided by 1
Like, 0.75/1
Step 2:
Now multiply both the numerator and denominator by 100.
We will multiply the numerator and denominator by 100 because 1.75 has two values after the decimal.
0.75 *100/1*100
75/100
Step 3:
Simplify the fraction.
divide the fraction by 5.
=15/20
=3/4
Now bring back the 1: and the fraction will become.
1 3/4
Jane drank 1 3/4 quarts of water.
Now who drank more water?
Jane drank more water than Tom
Reason:
Tom drank 1 1/4 = 5/4
Jane drank 1 3/4 = 7/4
Both the fractions have same denominator, so the value with the greater numerator drank more water than the other.
Therefore Jane drank more water than Tom....
28 greater than r is less than 308.
Answer:
r<280
Step by step explanation:
Subtract 28 from both sides of the equation r+28<308.
r+28 subtracted by 28 leaves us with r<.
308-28 is 280.
Hence the equation becomes r<280.
The expression or inequality is 28 > r < 308 which represents 28 greater than r is less than 308.
What is an expression?It is defined as the combination of constants and variables with mathematical operators.
The question is incomplete.
The complete question is:
Write the expression for the word expression "28 greater than r is less than 308"
It is given that:
The statement is:
28 greater than r is less than 308:
Here r is the real number.
Inequality can be defined as the expression in mathematics in which both sides are not equal they have mathematical signs either less than or greater than known as inequality.
28 > r < 308
Thus, the expression or inequality is 28 > r < 308 which represents 28 greater than r is less than 308.
Learn more about the expression here:
brainly.com/question/14083225
#SPJ2
What is m∠AKE? 120 60 70 110
Check the picture below.
We are asked to find m ∠AKE, which is the measure of angle MAK. Therefore, MAK = 70 degrees. So, m∠AKE = 70 degrees.
To find m∠AKE, we need to use the properties of angles in a triangle. First, let's identify the triangle we are dealing with. Based on the information provided, we have the following triangle:
A
/ \
/ \
/_____\
K E
Given that MAB = 110 and MDE = 130, we can use the fact that the sum of angles in a triangle is 180 degrees.
Since A is a common vertex to both angles MAB and MAE, we can write:
MAB + MAE + MAK = 180
Substitute the given values:
110 + MAE + MAK = 180
Now, we need to find MAE + MAK:
MAE + MAK = 180 - 110
MAE + MAK = 70
We are asked to find m∠AKE, which is the measure of angle MAK. Therefore, MAK = 70 degrees.
So, m∠AKE = 70 degrees.
To know more about angle here
https://brainly.com/question/25716982
#SPJ2
helppp it's timed
Study the equations:
f(x)=11x-5
g(x)=-2x-4
What is h(x)= f(x) g(x)?
A) h(x)=-22x^2+34x+20
B) h(x)=-22x^2+10x-24
C) h(x)=22x^2-54x+20
D) h(x)=-22x^2-34x+20
Answer:
D.
Step-by-step explanation:
h(x)=f(x)g(x) means multiply the expression for f to the expression for g.
That is the problem is just asking you to do (11x-5)(-2x-4).
Let's use foil.
First: 11x(-2x)=-22x^2
Outer: 11x(-4)=-44x
Inner: -5(-2x)=10x
Last: -5(-4)=20
------------------------Add together!
-22x^2-34x+20
D.
h(x) = [tex]-22x^{2} -34x+20[/tex]
Option D is correct.
What is an equation?An equation is a mathematical statement that is made up of two expressions connected by an equal sign.
Given equations
f(x) = 11x - 5
g(x) = - 2x - 4
h(x) = f(x) g(x)
h(x) = [tex](11x -5) \times (-2x-4)[/tex]
h(x) = [tex]11x \times (-2x) +11x \times (-4) -5 \times (-2x) -5 \times (-4)[/tex]
h(x) = [tex]-22x^{2} -44x+10x+20[/tex]
h(x) = [tex]-22x^{2} -34x+20[/tex]
Option D is correct.
Find out more information about equation here
brainly.com/question/2263981
#SPJ2
Anna wants to take fitness classes. She compares two gyms to determine which would be the best deal for her. Fit Fast charges a set fee per class. Stepping Up charges a monthly fee, plus an additional fee per class. The system of equations models the total costs for each.
y = 7.5x
y = 5.5x + 10
1. Substitute: 7.5x = 5.5x + 10
How many classes could Anna take so that the total cost for the month would be the same?
Answer:
y = 7.5x and y = 5.5x + 10
Step-by-step explanation:
this is for if you get the graph or not!
Answer:
5 classes
37.50 monthly cost for both gyms
Step-by-step explanation:
2022 edge
A card is drawn from a standard deck of 52 cards. What is the theoretical probability, as a decimal, of drawing an ace? Round the decimal to the nearest hundredth. (Hint: A standard deck of 52 cards contains 4 aces.)
P(ace) =
Answer:
0.08
Step-by-step explanation:
A standard deck of 52 cards has four aces.
The sample space is:
n(S) = 52
Let A be the event that an ace is drawn from the deck.
Then,
n(A) = 4
So,
[tex]P(A) = \frac{n(A)}{n(S)}\\ =\frac{4}{52} \\=0.0769[/tex]
Rounding off to the nearest hundredth will give us:
0.08 ..
The theoretical probability of drawing an ace from a standard deck of 52 cards is 0.08. The calculation is based on dividing the number of aces (4) by the total number of cards (52).
Explanation:The theoretical probability of an event occurring is calculated by dividing the number of ways an event can occur by the total number of possible outcomes. In this scenario, the question is asking about the theoretical probability of drawing an ace from a standard deck of 52 cards.
In a standard deck of cards, there are 4 aces. So, the number of ways the event 'drawing an ace' can occur is 4. The total number of possible outcomes, which is the total number of cards in the deck, is 52. Therefore, the probability of drawing an ace, P(Ace), is calculated as follows:
P(ace) = Number of aces in the deck / Total number of cards
P(ace) = 4 / 52
When you simplify this fraction or convert it into decimal form (rounded to the nearest hundredths), it gives:
P(ace) = 0.08
So, the theoretical probability of drawing an ace from a deck of 52 cards is 0.08.
Learn more about Theoretical Probability here:https://brainly.com/question/28040792
#SPJ12
There are 454 grams in a pound. There are 16 ounces in a pound. How many grams are in an ounce? (PLZZZ HELP)
Answer:
1 Ounce = 28.3495231 Grams
Step-by-step explanation:
Answer:
28.38 grams to the nearest hundredth.
Step-by-step explanation:
By proportion there is 454 / 16
= 28.38 grams in an ounce.
The table represents the multiplication of two binomials.
What is the value of A?
A: -3x
B: -3x^2
C: -5x
D: -5x^2
Answer:
B
Step-by-step explanation:
The entry A is the result of multiplying - x and 3x, that is
- x × 3x = - 3x² → B
Answer:
-3x^2
Step-by-step explanation:
A 3x * -x = -3x^2 so A = -3x^2
We can also find the value of B
B -x *5 = -5x
and C
C = 3x*2 = 6x
What is the length of one leg of the triangle?
Answer:
The correct answer is third option. 22 units
Step-by-step explanation:
Points to remember
If a right angled triangle with angles are 45°, 45° and 90° then the sides are in the ratio 1 : 1 : √2
To find the length of one leg of the triangle
From the figure we can see a right angled triangle with hypotenuse = 22√2 units
The other two legs are equal. Therefore the right angled triangle with angles 45°, 45° and 90°
Therefore the given triangle sides are in the ratio,
1 : 1 : √2 = x : x : 22√2
Therefore x = 22 units
The correct answer is third option. 22 units
Which expression is equivalent to!!!!!
Answer:
A
Step-by-step explanation:
Use the property
[tex]\sqrt[n]{a^m}=a^{\frac{m}{n}}[/tex]
The numerator can be simplified as
[tex]\sqrt[7]{x^2}=x^{\frac{2}{7}}[/tex]
The denominator can be simplified as
[tex]\sqrt[5]{y^3}=y^{\frac{3}{5}}[/tex]
Also remindr property
[tex]\dfrac{1}{a^n}=a^{-n}[/tex]
Thus, the expression is equivalent to
[tex]\dfrac{\sqrt[7]{x^2} }{\sqrt[5]{y^3} }=\dfrac{x^{\frac{2}{7}}}{y^{\frac{3}{5}}}=\left(x^{\frac{2}{7}}\right)\cdot \left(y^{-\frac{3}{5}}\right)[/tex]
What is the solution to –4(8 – 3x) ≥ 6x – 8?
Answer:
x ≥ 4
Step-by-step explanation:
Given
- 4(8 - 3x) ≥ 6x - 8 ← distribute parenthesis on left side
- 32 + 12x ≥ 6x - 8 ( subtract 6x from both sides )
- 32 + 6x ≥ - 8 ( add 32 to both sides )
6x ≥ 24 ( divide both sides by 6 )
x ≥ 4
Answer:
x ≥ 4
Step-by-step explanation:
4(8 - 3x) ≥ 6x - 8 distribute parenthesis on left side
32 + 12x ≥ 6x - 8 (subtract 6x from both sides)
32 + 6x ≥ - 8 (add 32 to both sides)
6x ≥ 24 (divide both sides by 6)
= x ≥ 4
distribute and simplify (√12 + 6)(- √8 - √2)
Answer
-18√2-6√6
Step-by-step explanation:
(√12 +6) (-√8-√2)
=√12(-√8-√2)+6(-√8-√2)
= -√96-√24-6√8-6√2
= -4√6-2√6-12√2-6√2
= -6√6-18√2
= -18√2- 6√6
need proof that ABCD is a parallelogram
Step-by-step explanation:
To prove that two sides are parallel on a graph, we must show that their slopes are the same. Plotting this on Desmos, we get the first image attached. Finding the slopes of each line, we get
[tex]TOP\\\frac{5-3}{6-1} =2/5\\BOTTOM\\\frac{-1-(-1)}{7-2} =2/5\\RIGHT\\-4\\LEFT\\-4[/tex]
As the top slope is the same as the bottom, and the right is the same as the left, this is a parallelogram.
To prove that two sides are congruent, we must find their lengths. The distance formula is
[tex]\sqrt(x_{1}+x_{2})^2+(y_{1}+y_{2})^2 } \\[/tex]
Finding the distances, we get
TOP: [tex]\sqrt{29}[/tex]
BOTTOM: [tex]\sqrt{29}[/tex]
RIGHT:[tex]\sqrt{17}[/tex]
LEFT:[tex]\sqrt{17}[/tex]
As the lengths are the same, the sides are congruent